ESTUDIOS SOBRE LA MEDULA OSEA VII DATOS NUMERICOS DEL MIELOGRAMA DEL CONEJO NORMAL - GONZALEZ GUZMAN, IGNACIO (Universidad Nacional Autónoma de Mexico, Instituto de Biología, CD MEXICO, DF, MEX, 1947)
Starting from a previous hypothesis, according to which protein loosely linked with certain mucopolysaccharides represents the protein storage utilized for cell growth, the authors investigated the effects of subcut injn in rats of ocular fluids rich in
BOL MEN BAN REF JAL
Keywords: ESTUDIOS, MEDULA OSEA, DATOS NUMERICOs, MIELOGRAMA, CONEJO NORMAL; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL